The European Association of Urology Robotic Urology Section (ERUS) survey of robot-assisted radical prostatectomy (RARP). - Ficarra, V; Wiklund, P; Rochat, C; Dasgupta, P; Challacombe, B; Sooriakumaran, P; Siemer, S; Suardi, N; Novara, G; Mottrie, A (2013)
OBJECTIVE: To evaluate surgeons adherence to current clinical practice, with the available evidence, for robot-assisted radical prostatectomy (RARP) and offer a baseline assessment to measure the impact of the Pasadena recommendations. Recently, the European Association of Urology Robotic Urology Section (ERUS) supported the Pasadena Consensus Conference on best practices in RARP. SUBJECTS AND METHODS: This survey was performed in January 2012. A specific questionnaire was sent, by e-mail, to 145 robotic surgeons who were included in the mailing-list of ERUS members and working in different urological institutions. Participating surgeons were invited to answer a multiple-choice questionnaire including 24-items evaluating the main RARP surgical steps. RESULTS: In all, 116 (79.4%) invited surgeons answered the questionnaire and accepted to participate to the ERUS survey. In all, 47 (40.5%) surgeons performed >100 RARPs; 41 (35.3%) between 50 and 100, and 28 (24.1%) <50 yearly. The transperitoneal, antegrade technique was the preferred approach. Minimising bladder neck dissection and the use of athermal dissection of the neurovascular bundles (NVBs) were also popular. There was more heterogeneity in the use of energy for seminal vesicle dissection, the preservation of the tips of the seminal vesicle and the choice between intra- and interfascial planes during the antero-lateral dissection of the NVBs. There was also large variability in the posterior and/or anterior reconstruction steps. CONCLUSIONS: The present study is the first international survey evaluating surgeon preferences during RARP. Considering that the results were collected before the publication of the Pasadena recommendations, the data might be considered an important baseline evaluation to test the dissemination and effects of the Pasadena recommendations in subsequent years.